Baraclayan pagyamanin sa wastong pagkain - Amihan, April Rose D.; Basco, Arriane Mae P.
Malnutrition is a major health problem, especially in developing countries. Water supply, sanitation and hygiene, given their direct impact on infectious dsease, especially diarhea, are important for preventing malnutrition. Malnutrition affects all age groups, but it is especially commong among the poor and those with inadequate acces to heslth education and to clean water and good sanitation. The project primarily aimed o reduce the incidence of malnutrition in the community by at least 50%. The project achieved its goal through feeding program to increase the utrients intake of children, and health education to increase the level of knowledge of mothers regarding proper, nutrition, child care and breastfeeding practices, and increase the level of knowledge of children regarding proper hygiene and sanitation.